Reconciling Quality by Design and Transdermal Product Development - Kenneth Miller (MDPI AG, 2020)
Since my first exposure to the acronym ‘QbD’ more than ten years ago, I have been trying to understand exactly what QbD is and how I might incorporate its teachings into my twenty-odd years of experience developing transdermal systems. I feel I have made little progress since then. Eventually, I came to realize that while QbD has its merits, it is not a guide for (transdermal) product development, despite so often being described as such. Instead, I have come to consider QbD as a language useful for organizing and presenting the array of data supporting the approval of a new product, but it still leaves the experimental approach entirely up to the developer. What QbD does provide to the development community is a means of conveying product information through a consistent framework facilitating both internal and regulatory review. As a result, new ‘QbD’ product applications tend to be more uniform and complete than the applications that preceded the initiative.